An Analysis of Oxidative Changes and the Fatty Acid Profile in Stored Poultry Sausages with Liquid and Microencapsulated Fish Oil Additives - Krzysztof Kawecki; Jerzy Stangierski; Piotr Konieczny (Molecules, 2021)
This study deals with the fatty acid profile and oxidative changes (TBARS) in vacuum-packed (VP) or modified-atmosphere-packed (MAP) finely-comminuted poultry sausages with liquid fish oil and microencapsulated fish oil (MC) additives. An analysis of omega-3 fatty acids (EPA and DHA) showed that their content in the samples with the fish oil additive decreased from the initial value of 0.22 g∙100 g−1 of the product to 0.18 g∙100 g−1 (MAP) and 0.17 g∙100 g−1 (VP), respectively. After in vitro digestion, the total EPA and DHA content in the sample with microencapsulated oil amounted to 0.17 g∙100 g−1 of the product. The TBARS values showed the VP samples with both forms of the fish oil additive had the lowest values on the first day of storage. Storage of the samples for 21 days caused a slight increase in the degree of lipid oxidation. The research indicated that the forms of the oil additive did not have a negative influence on the sensory features or the physicochemical properties of the sausages. The EPA and DHA levels in samples with liquid fish oil and those with oil microcapsules were sufficient for the sausage producer to declare high content of these fatty acids in accordance with the current EC regulation.